Improving The Quality of Islamic Religious Education Learning Through Revitalization of Teacher Deliberations of Islamic Religious Education Subjects - Lukman Al Hakim; Ulfiah Ulfiah; Fahruroji Fahruroji; Usep Kosasih (Syntax Corporation Indonesia, 2022)
This study aims to examine improvement of the quality of PAI learning through revitalization of the Subject Teacher Conference. This research is based on several thoughts and theories, including; Surah Al-Raad verse 11, which implies that humans must change life for the better through education as a provision for life. Then philosophically, there is a view that education is oriented to the nature of knowledge and a better life. While the theory used is the theory of learning and achievement. In addition, this study uses a qualitative method or approach in which the author tries to examine phenomena and theories from a pragmatic perspective. The results of this study are; the purpose of MGMP Revitalization is to improve learning quality based on the Indonesian Government Regulation number 19 of 2005 concerning National Education Standards. The things that are emphasized are student center methods, professionalism, and active learning. Furthermore, the implementation applied is the application of innovative learning processes, dedication to the mission and vision, empowerment of human resources, and training for teachers. Finally, the problem is that professionalism, knowledge, abilities, and skills are not optimal. At the same time, the solutions and efforts taken are the emphases on having mastery of planning, mastering various competencies, the attitude of teacher responsibility in learning, and high motivation